2018
DOI: 10.3382/ps/pey147
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and antimicrobial susceptibility of Campylobacter spp. on fresh and refrigerated chicken meat products in Central Italy

Abstract: This study investigated the presence and the level of Campylobacter spp. contamination in 41 thigh samples (with skin) and 37 skinless breast samples collected at the end of slaughter (T1) and after 10 day period at refrigeration temperature (4°C) (T2), corresponding to their commercial shelf life. The isolates were phenotypically classified as Campylobacter spp. and successively identified by conventional multiplex PCR. The antimicrobial susceptibility of the isolates from fresh thigh and breast samples was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
3
5
0
Order By: Relevance
“…Additional assays, such as PCR, improve the discrimination between Campylobacter strains ( Gharst et al., 2013 ). However, consistent with these findings, earlier research found that C. jejuni was more prevalent than C. coli in poultry samples ( Giombelli and Gloria, 2014 , Panzenhagen et al., 2016 , Casagrande Proietti et al., 2018 , Rossler et al., 2019 ). Note that in the present study, however, the majority of C. jejuni strains were isolated in Preston agar.…”
Section: Resultssupporting
confidence: 73%
“…Additional assays, such as PCR, improve the discrimination between Campylobacter strains ( Gharst et al., 2013 ). However, consistent with these findings, earlier research found that C. jejuni was more prevalent than C. coli in poultry samples ( Giombelli and Gloria, 2014 , Panzenhagen et al., 2016 , Casagrande Proietti et al., 2018 , Rossler et al., 2019 ). Note that in the present study, however, the majority of C. jejuni strains were isolated in Preston agar.…”
Section: Resultssupporting
confidence: 73%
“…Although an in vitro analysis have shown the ability of Campylobacter coli Brazilian strains to grow at 4°C for 24 hours in microaerobic conditions, after inoculation in Brain Heart Infusion (BHI) broth (Gomes et al, 2018), it should be noted that thermotolerant Campylobacter are unable to multiply in foods under retail or household storage at low temperatures (Ritz et al, 2007;Membré et al, 2013;Al-Sakkaf, 2015). As found in the present study, the reduced level of C. jejuni during chilled storage of chicken has been reported in comparison with the initial contamination level (Sampers et al, 2010;Casagrande Proietti et al, 2018), but without achieving the pathogen inactivation. Therefore, storage at 4°C offers a risk of transfer of residual surviving Campylobacter from contaminated chicken.…”
supporting
confidence: 69%
“…are fastidious bacteria, sensitive to high and low temperatures (Al-Sakkaf, 2015;Hansson et al, 2018). Therefore, physical interventions, such as chilling or freezing, reduce the contamination of chicken (Sampers et al, 2010;Boysen et al, 2013;Casagrande Proietti et al, 2018) and may result in a lower risk of consumer infection. Nevertheless, retail storage conditions for poultry meat often facilitate the Campylobacter survival at lower temperatures (Ritz et al, 2007;Hansson et al, 2018), while safety at the consumer stage relies on domestic kitchen practices, including food hygiene and appropriate cooking (Membré et al, 2013;Al-Sakkaf, 2015;Langsrud et al, 2020).…”
mentioning
confidence: 99%
“…Another factor is the kind of sample evaluated (skin vs. meat). EFSA [ 24 ] mentions that removing the skin from chicken breast cuts reduces the number of Campylobacter . Likewise, Casagrande et al [ 25 ] reported a more significant number of positive samples for Campylobacter in chicken cuts with skin (82.9%) compared to skinless (48.6%).…”
Section: Discussionmentioning
confidence: 99%